Analisis Tindak Tutur Dalam Film Tanah Air Beta Karya Ari Sihasale - Windy Wonmaly; Desi Susana Arwam; Tirsa Lingchin; Vicky Lendehiang; Allin Leunufna (CV. ITTC INDONESIA, 2023)
This study aims to determine the forms of locutionary, illocutionary, and perlocutionary speech acts contained in a film entitled